2019
DOI: 10.3233/jad-170578
|View full text |Cite
|
Sign up to set email alerts
|

Regional Tau Correlates of Instrumental Activities of Daily Living and Apathy in Mild Cognitive Impairment and Alzheimer’s Disease Dementia

Abstract: Background: Instrumental activities of daily living (IADL) impairment and apathy occur in early-stage Alzheimer’s disease (AD) and are associated with regional atrophy and hypometabolism in vivo and greater tau burden at autopsy. Objective: To explore the association between IADL impairment, apathy, and in vivo regional tau in mild cognitive impairment (MCI) and AD dementia. Methods: Forty participants (24 MCI, 16 AD dementia) underwent assessments of IADL (Functional Activities Questionnaire, FAQ) and apa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 63 publications
1
26
0
Order By: Relevance
“…From these facts, "writing" may be associated with spontaneity. In addition, previous studies have also reported that spontaneity is strongly associated with IADL [35,36]. Therefore, since "writing" has a feature that requires spontaneity and multiple cognitive functions such as executive function and visual-spatial cognitive function, it may have suggested a strong association with IADL.…”
Section: Discussionmentioning
confidence: 95%
“…From these facts, "writing" may be associated with spontaneity. In addition, previous studies have also reported that spontaneity is strongly associated with IADL [35,36]. Therefore, since "writing" has a feature that requires spontaneity and multiple cognitive functions such as executive function and visual-spatial cognitive function, it may have suggested a strong association with IADL.…”
Section: Discussionmentioning
confidence: 95%
“…Disturbances in drive and emotions in AD are often referred to as manifestations of frontal lobe pathology, wherefore an association with temporal tau deposition could be considered a somewhat unexpected finding in its relation to neuropsychiatric symptoms. Yet, most pathological studies displaying such frontal associations have been conducted on MCI and AD dementia samples, not on CU samples 27 , 28 . Some studies focusing on cerebral atrophy have instead strengthened the role of the temporal lobe pathology in neuropsychiatric and behavioral symptoms, such as apathy, among CU subjects 29 , 30 .…”
Section: Discussionmentioning
confidence: 99%
“…For example, apathy is more common in those with neurofibrillary tangles in the left ACC than it is in those with predominant Alzheimer disease pathology in other areas. 43,80 In addition, in vivo analysis demonstrates an association between apathy severity and tau deposition in the ACC and DLPFC, 81 as well as amyloid-b deposition throughout the bilateral frontal cortex and right ACC. 63 Parkinson Disease.…”
Section: Neuroanatomical Abnormalities Of Apathy In Brain Injury and mentioning
confidence: 99%